Global Results of Implantable Loop Recorder for Detection of Atrial Fibrillation After Stroke: Reveal LINQ Registry - Kazunori Toyoda; Kengo Kusano; Yasuyuki Iguchi; Takanori Ikeda; Itsuro Morishima; Hirofumi Tomita; Taku Asano; Teiichi Yamane; Ichiro Nakahara; Eiichi Watanabe; Junjiroh Koyama; Ritsushi Kato; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background We aimed to quantify the incidence of atrial fibrillation (AF) in patients with cryptogenic stroke globally, as well as separately in patients in and outside of Japan, using an implantable loop recorder from a prospective, observational, Reveal LINQ Registry. Methods and Results Patients developing cryptogenic stroke and monitored by implantable loop recorder for searching AF were studied. The primary end point was incidence of AF within 36 months after insertion. Secondary end points were recurrent ischemic stroke/transient ischemic attack and AF‐related treatment strategies. A total of 271 patients (61.6±14.3 years, 170 men, 60 from Japan) were enrolled from 12 countries. AF was detected in 28.2% at 36 months. The median time from enrollment to AF detection was 7.9 months. During the first 12 months, the AF detection rate slope was relatively steeper in the Japanese subgroup versus non‐Japanese patients. However, by 3 years, the cumulative incidence of AF detection did not differ between groups. Age was the only variable associated with AF detection (hazard ratio, 1.05 [95% CI, 1.02–1.07] per year), trending higher in older age groups. Of the 271 patients, 11 (4.1%) developed recurrent ischemic stroke/transient ischemic attack; AF was detected by implantable loop recorder in only 1 of these patients. Patients with detected AF were more commonly taking oral anticoagulation than those without AF at the last follow‐up (64.7% versus 25.3%, P<0.001). Conclusions The rate of AF detection was similar to other studies in stroke populations monitored by implantable loop recorders, including CRYSTAL‐AF (Cryptogenic Stroke and Underlying Atrial Fibrillation), STROKE‐AF (Stroke of Unknown Cause and Underlying Atrial Fibrillation) and PER‐DIEM (Post‐Embolic Rhythm Detection With Implantable Versus External Monitoring). Patients with detected AF more commonly initiated anticoagulation than those without AF.